Accuracy and revision rate of intraoperative computed tomography point-to-point navigation for lateral mass and pedicle screw placement: 11-year single-center experience in 1054 patients - Ishak, Basem; Younsi, Alexander; Wieckhusen, Carola; Slonczewski, Paula; Unterberg, Andreas; Kiening, Karl (Neurosurgical review, 2019)
High accuracy in intraoperative computed tomography (iCT) navigation utilizing an intraoperatively acquired dataset for screw placement in the spine has been reported in the literature. To further improve the accuracy and counteract any intraoperative movement of predefined registration points, we introduce an iCT point-to-point navigation, where marker screws are inserted intraoperatively to increase patient safety. In all, 1054 patients who underwent iCT point-to-point navigation for lateral mass and pedicle screw placement were retrospectively analyzed between 09/2005 and 09/2016. Implant-related complications such as screw misplacement, screw loosening, and revision rate were determined. Furthermore, we investigated the rate of complications and the clinical outcome. In total, 6059 screws were inserted in 1054 patients. There were 553 (52.5%) female and 501 (47.5%) male patients. Average age was 63.5 years, mean BMI 27.5 (SD 13.9). Here, 1427 (23.5%) screws were inserted in the cervical, 995 (16.4%) in the thoracic, 3167 (52.3%) in the lumbar, and 470 (7.8%) in the sacral spine. Eight patients required a revision procedure for screw misplacement (0.8%). Total screw misplacement rate was 0.3% (16/6059). With the use of reference markers in iCT-based, spinal, point-to-point navigation, we achieved a high accuracy of screw placement with a low revision rate (0.8%) and a total screw misplacement rate of 0.3%.